Advances in applied microbiology (Elsevier, 2014)
The series contains comprehensive reviews of the most current research in applied microbiology. Recent areas covered include bacterial diversity in the human gut, protozoan grazing of freshwater biofilms, metals in yeast fermentation processes and the interpretation of host-pathogen dialogue through microarrays.